Faktor Yang Mempengaruhi Minat Penggunaan Mobile Banking - Harries Arizonia Ismail; Tri Purwani (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
This study aims to analyze the five hypotheses proposed including the effect of perceived suitability on perceived usefulness, the effect of perceived suitability on perceived ease of use, the effect of perceived ease of use on perceived usefulness, the effect of perceived usefulness on intention to use and the effect of perceived ease of use on intention to use. The population in this study were students of AKI University in Semarang. The sampling technique used was purposive sampling. The number of samples represented 94 respondents. The data collected were analyzed using the Structural Equation Modeling (SEM) approach and processed with the AMOS program. The result of the hypothesis shows the influence of perceived compatibility toward perceived usefulness is positively, the influence of perceived compatibility toward perceived ease of use is positively, the influence of perceived ease of use toward perceived usefulness is positively, the influence of perceived usefulness toward intention to use is is positively, and also the influence of perceived ease of use toward intention to use is positively. The results of this study prove that intention to use Mobile Banking is influenced by the perception of usefulness and the perception of ease of use which is influenced by the perceived suitability factor.